Przepisy prawa regulujące nadanie i zmianę imienia i nazwiska jako narzędzie formowania nowego społeczeństwa w państwach o ustrojach niedemokratycznych – część I - Behr, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The subject of the article are legal regulations concerning giving and changing names and surnames, analysed in the context of their role in the formation of society in countries with non-democratic systems, including the creation of a model member of such a society. Administrative law and administration will be shown as a tool serving the current interests of the ruling power. The importance of the name and surname in shaping a person’s personality and strengthening his relationship with a specific group will be explained, and the consequences of changes in this area will be indicated. The article will also highlight and discuss two types of provisions of legal acts regulating the granting and changing of a name and surname. The former make it possible to separate the model members of the new society from its enemies and make it easier to identify and eliminate undesirable people (laws in force in the Third Reich). The second enables the creation of a homogeneous society through the forced assimilation of selected individuals (laws in force in People’s Poland aimed at de-Germanisation). The article uses the legal-dogmatic method, consisting in the analysis and interpretation of the texts of legal acts, and the historical and legal method, taking into account the changes of the analysed legal institution over the years. The work also takes into account the practice of applying the law in the researched area.
Keywords: change of name and surname; formation of a new society; Third Reich; People’s Poland; anti-Jewish laws; de-Germanisation